The Story of the Movie - Willis, Jeanne (UK, 2014)
When a young bear arrives in London in search of a new home, he soon finds himself caught up in a thrilling adventure. Befriended by the Brown family, Paddington is also spotted by Millicent, a sinister taxidermist at the Natural History Museum. Can he outsmart Millicent and avoid ending up in her stuffed animal collection?...
Keywords: Animal Adventure; Bear; Juvenile Fiction